The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3174/ajnr.a3168
|View full text |Cite
|
Sign up to set email alerts
|

Technical Feasibility and Application of Mechanical Thrombectomy with the Solitaire FR Revascularization Device in Acute Basilar Artery Occlusion

Abstract: BACKGROUND AND PURPOSE:Acute BAO is a devastating neurological condition associated with a poor clinical outcome and a high mortality rate. Recanalization has been identified as a major prognostic factor for good outcome in BAO. Mechanical thrombectomy using retrievable stents is an emerging treatment option for acute stroke. First clinical trials using stent retrievers have shown promising high recanalization rates. However, these studies mainly included large artery occlusions in the anterior circulation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
78
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 35 publications
11
78
3
Order By: Relevance
“…Recent studies with the use of mechanical thrombectomy with stent retrievers reported significantly increased recanalization rates ranging from 74 -100% in patients with acute BAO. [12][13][14] In our study, we achieved successful recanalization (TICI grades 2b to 3) in 96% (24/25) of patients, which is in line with previous reports. Successful recanalization with only the Solitaire stent occurred in 84% (21/25) of patients.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Recent studies with the use of mechanical thrombectomy with stent retrievers reported significantly increased recanalization rates ranging from 74 -100% in patients with acute BAO. [12][13][14] In our study, we achieved successful recanalization (TICI grades 2b to 3) in 96% (24/25) of patients, which is in line with previous reports. Successful recanalization with only the Solitaire stent occurred in 84% (21/25) of patients.…”
Section: Discussionsupporting
confidence: 80%
“…[12][13][14] In contrast to our study, these previous studies included patients treated within 24 hours of stroke symptom onset. In a series of 14 patients treated with a Solitaire thrombectomy, Mordasini et al 12 reported that 28.6% (4/14) had a good outcome (mRS 0 -2), and the mortality rate was 35.7% (5/14). In their study, a Solitaire thrombectomy was not the first-line endovascular treatment, and the median time from symptom onset to first angiogram was 414 minutes (range, 176 -1440 minutes).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The Solitaire endovascular device has proved to be a valid tool in the treatment of acute ischemic stroke, providing effective and relatively safe arterial recanalization. 11,12,21,22 In our study of FPCT after endovascular stroke treatmentwith IV bridging thrombolysis in 10%, intra-arterial thrombolysis in 56%, and mechanical thrombectomy in 81% of patients-an intracranial hematoma was present in 16% of all cases. While most ICB (5% of patients) was found to be a clinically less relevant hemorrhagic transformation, parenchymal hematoma was a rare incident (4%); however, it was combined with SAH in all 3 cases.…”
Section: Discussionmentioning
confidence: 99%
“…3 Early recanalization remains the main important factor that can improve outcome. [4][5][6] However, even though the best recanalization rate is achieved by using a newer stent retriever, such as a Solitaire FR Device (Covidien, Irvine, California) (up to 100%), [7][8][9][10] stent retriever impact on functional outcome is not as clear-cut as expected and has not been documented in a randomized trial. The extent of baseline brain stem ischemic damage can also influence outcome.…”
mentioning
confidence: 99%